Receipt of diabetes preventive care among safety net patients associated with differing levels of insurance coverage - Gold, Rachel (2012)
BACKGROUND: Patients receive care in safety net clinics regardless of insurance status; however, diabetes preventive care receipt might vary in patients with differing levels of insurance continuity. METHODS: In a retrospective cohort study, using electronic health record data from adults with diabetes receiving care in 50 safety net clinics in Oregon in 2005–2007, we conducted adjusted logistic regressions to model the associations between amount of time with insurance and rates of receipt of lipid screening, influenza vaccination, nephropathy screening (urine microalbumin), and DM control (glycosylated hemoglobin) screening. RESULTS: Of 3,384 adults with diabetes, 711 were ‘partially’ insured (covered 1–99% of the 3-year study period), 909 had no coverage, and 1,764 were continuously insured. In adjusted models, persons with partial or no coverage during the 3-year study period were less likely to receive most preventive services, compared to those with continuous coverage. We found no evidence of a dose-response relationship with increasing duration of coverage, nor of a threshold amount of partial coverage, associated with better receipt of care. CONCLUSIONS: Safety net clinic patients need both access to primary care and continuous insurance. All patients with partial coverage, regardless of the extent of time with insurance, had lower odds of receiving preventive care.